Water monitoring system for agriculture sector - Intan Shafinaz, Mohammad (Universiti Malaysia Perlis, 2008)
Nowadays robotic and automation system has been introduced to facilitate humankind from doing everyday chores to the high scale manufacturing. The agriculture sector is very important for country to generate economy throughput optimization and better product quality. Therefore, it needs the modern irrigation system. Based on that requirement, the water monitoring system has been developed. The water levels in tank automatically control the pump. It also can monitor with the interfacing system. Visual Basic software is used as software tool to produce a graphic user interface (GUI). The distance sensor was detecting the water level and give data to the microcontroller. The microcontroller will process the data and control the pumping system to allow the amount of water that will be flow into the tank. The processed data from microcontroller will be sent to the computer and display the water level in the tank.